The effect of bleaching applications on stained bulk-fill resin composites - Ayse Tugba Erturk-Avunduk; Esra Cengiz-Yanardag; Izgen Karakaya (BMC, 2022)
Abstract Background The structure of bulk-fill resin composites differs from that of their conventional counterparts, but how this difference affects the color stability of the former after staining and bleaching is unclear. Accordingly, this study was aimed at investigating color change in nine bulk-fill resin composites and one nanohybrid resin composite treated with hydrogen peroxide and carbamide peroxide after staining with tea, coffee, and red wine. Methods Eighty specimens were prepared from each resins [Clearfil Majesty Posterior (CMP), SDR flow+ (SDR), FiltekTMBulk-Fill Flowable Restorative (FBF), Reveal HD Bulk (RHD), Beautifil-Bulk Restorative (BBR), Tetric EvoCeram® Bulk Fill (TEC), SonicFill™2 (SF2), everX Posterior™ (eXP), X-tra base (XB), and Venus® Bulk Fill (VBF)]. Following baseline color measurements, the specimens were randomly divided into 4 groups according to immersion solutions and distilled water as the control. At the end of a 30-day test period, color measurements were repeated, and color change values (∆E00) were calculated. Each resin group was then divided into 2 subgroups (with 10 specimens per group) on the basis of bleaching agent (Opalescence Boost 40%, Opalescence PF 16%). Following bleaching application, ∆E00 and changes of whiteness (∆WID1 = WIDbleaching-WIDbaseline, ΔWID2 = WIDbleaching-WIDstaining) values were recorded. Two- and three-way analyses of variance and Tukey's post hoc test were performed, with a P < 0.05 regarded as indicative of significance. Results After immersion in distilled water, tea, and red wine, the highest ΔE00 values were observed in eXP (P < 0.05). Resin materials immersed in coffee and tea exhibited statistically higher ∆E00 values than those immersed in red wine except for eXP, TEC, and FBF (P < 0.05). For eXP, the highest ∆E00 values were recorded in distilled water. For TEC and FBF, there was no statistically significant difference among the immersion solutions and distilled water (P > 0.05). For all the resins and staining beverages, no statistically significant difference in ∆WID1 and ∆WID2 values were detected between bleaching agents (P > 0.05). All the ΔWID1 values were above the whiteness perceptibility threshold. Conclusion The bulk-fill materials were more resistant to discoloration and bleaching procedures than the conventional resin composites. Coffee and tea caused more staining than distilled water and red wine generally. The type of bleaching procedure had no effect on the whiteness of the tested materials.